Evidence of hetero-epitaxial growth of Pb(Mg1/3Nb2/3)O-3 on the BaTiO3 seed particles of a citrate solution - Spagnol, P. D.; Varela, José Arana [UNESP]; Zaghete, M. A.; Longo, Elson [UNESP]; Tebcherani, S. M. (Elsevier B.V., 2003)
Citrate solution was employed in preparing Pb(Mg1/3Nb1/3)O-3 (PMN) powder from polymeric precursors. BaTiO3 particles of 600 nm average size were used as seed for growing PMN. X-ray diffraction (XRD) indicated the presence of both, pyrochlore Pb6Nb6MgO22 (P6N) and perovskite phases. Transmission electron microscopy (TEM) observations indicated that only the PMN phase has hetero-epitaxially grown on the BaTiO3 seed particles. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: BaTiO3; Pb(Mg1/3Nb2/3)O-3; perovskite; pyrochlore